Calcineurin Inhibitor–Based versus Cyclophosphamide-Based Immunosuppression for Primary Membranous Nephropathy: A Meta-Analysis of Remission and Relapse - Ligat Pribadi Sembiring; Harnavi Harun (Sriwijaya Journal of Internal Medicine, 2026)
Introduction. Primary membranous nephropathy (MN) is a leading cause of the nephrotic syndrome in adults. Calcineurin inhibitor (CNI)-based and cyclophosphamide-based regimens are both endorsed as first-line therapy, but their comparative efficacy and the durability of the remission they induce remain uncertain. This study was aimed to compare CNI-based versus cyclophosphamide-based regimens for total remission, complete remission and relapse in adults with primary MN. Methods. PubMed/MEDLINE, with Scopus and Web of Science indexing checks and manual reference screening, was searched for randomised controlled trials (RCTs) comparing a CNI-based regimen (tacrolimus or cyclosporine) with a cyclophosphamide-based regimen. Risk ratios (RRs) were pooled with a DerSimonian–Laird random-effects model; heterogeneity was quantified with I2. Risk of bias used the Cochrane RoB 2 tool. The review was not registered. Results. Nine RCTs (eleven articles; 599 participants) were included. Total remission did not differ between strategies (RR 1.02, 95% CI 0.86-1.20; I2=67%; 95% prediction interval 0.61-1.72; CNI 222/297 versus cyclophosphamide 215/302). Complete remission did not differ (RR 0.84, 95% CI 0.34-2.04). Relapse tended to be more frequent after CNI-based therapy (RR 1.76, 95% CI 0.95-3.24; I2=0%) without reaching significance. Estimates were stable across all sensitivity analyses (RR 0.91-1.11) and no small-study effect was detected (Egger p=0.87). Conclusion. CNI-based and cyclophosphamide-based regimens produced comparable remission in primary MN; a non-significant signal towards more frequent relapse after CNI therapy supports individualised, durability- and toxicity-aware treatment selection.